التقييد بالمفاعيل النحوية -رؤية بلاغية - هناء شيباني (University of Eloued جامعة الوادي, 2024)
"هذا البحث بعنوان؛ التقييد بالمفاعيل النحوية -رؤية بلاغية-مطبق على النص القرآني، في حدود نماذج مختارة منه، يطرح إشكالية رئيسية تتمثل في: ماهي الدلالات والأغراض البلاغية للتقييد بالمفاعيل النحوية؟ وكيف يؤثر هذا التقييد على جمالية المعنى؟ ولمعالجة هذا الاشكال سرت ضمن خطة بحثية تضمنت مبحثين، مبحث؛ تطرقت فيه لبيان وتعريف مصطلحات البحث (التقييد والمفاعيل الخمسة)، ومبحث؛ حاولت فيه الكشف عن بعض الأغراض البلاغية للتقييد بالمفاعيل النحوية من خلال استحضار ودراسة نماذج اخترتها من القرآن الكريم. ولعل أبرز ما توصلت اليه في هذه الدراسة، أن القيود وإن كانت فضلة كما يراها النحاة، الا أن وجودها في الجملة، له الأثر الكبير في تحديد المعنى وإبراز سماته، اذ إن البليغ يختار من احتمالي التقييد وعدمه، ما يراه محققا لغرض بلاغي يقصده، او يراه أوفى بتحقيقه بما يطابق به مقتضى حال. وأن المفاعيل الخمسة كلها من المقيدات، التي تعمل على تخصيص وتقييد جهات الفعل المختلفة، من حيث وقوع الحدث المتضمن فيه. وأن الأغراض البلاغية للتقييد بها، يصعب حصرها، فتتعدد وتختلف من مفعول لآخر، ومن مقام لآخر. " This research is entitled: Restriction to grammatical objects - a rhetorical vision - applied to the Qur’anic text, within the limits of selected examples of it, raises a major problem: What are the connotations and rhetorical purposes of restriction to grammatical objects? To address these problems, I followed a research plan that included two sections: one; In it, I touched on the clarification and definition of research terms (restriction and the five effects), and the topic: In it, I tried to reveal some of the rhetorical purposes of restricting grammatical objects by recalling and studying examples I chose from the Holy Qur’an. Perhaps the most prominent finding in this study is that restrictions, even if they are preferable as grammarians see them, are nevertheless present in the sentence. They have a great impact in determining the meaning and highlighting its features, as the eloquent person chooses from the possibilities of restriction or not, what he sees as fulfilling the rhetorical purpose he intends, or He considers it more fulfilling to achieve what is consistent with the requirements of the situation. All five effects are restrictions, which work to specify and restrict the various aspects of action, in terms of the occurrence of the event included in it. The rhetorical purposes to be restricted are difficult to limit, as they are numerous and differ from one object to another and from one position to another"
ماستر
Keywords: التقييد، المفاعيل النحوية، الأغراض البلاغية.; Restriction; grammatical effects; rhetorical purposes.